QuicTor: Enhancing Tor for Real-Time Communication Using QUIC Transport Protocol - Lamiaa Basyoni (16896426) (2021)
In the past decades, the internet has emerged as the fastest way to access information. However, this revolutionary information age comes with its own set of challenges. The privacy of Internet users is at increasing risk with the advances in surveillance techniques. Users' online behavior, activities, and even personal information are being tracked by ISPs and major tech companies. In response to the increasing need for preserving and protecting the privacy of online users, anonymity networks were developed. Tor anonymity network is a low-latency anonymity network that has gained quite a good reputation over the past years and is being adopted by thousands of users. With the great attention Tor's network is getting, the original design of Tor was proven to have performance limiting issues. With the motivation for addressing the performance limitation in Tor, we present QuicTor, a datagram-based design to solve Tor's transport-layer limiting issue. We evaluated the performance of QuicTor in comparison to vanilla Tor as well as other performance-enhancing proposals. QuicTor achieved significant performance improvements for interactive applications as well as streaming applications. Running Tor over a datagram-based protocol entails a careful security analysis. In this article, we assess the behavior of QuicTor under side-channel attacks aiming to de-anonymize Tor's clients. We show that the performance improvements brought by QuicTor do not reduce the anonymity of clients under the investigated types of attacks. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2021.3059672